Non-identity, sufficiency and exploitation - Rendall, Matthew (Wiley, 2011)
In this article I advance a solution to the non-identity problem based on distributive justice. Drawing on a seminal article by Gregory Kavka, I argue that in our everyday decisions about creating people, we widely recognize three principles. First, we should not conceive children whose lives are not worth living. Second, we believe that children, whenever possible, should enjoy a certain minimum level of well-being. This is consistent with what is known as the sufficiency view. Third, we believe children should receive their fair share of benefits and burdens. It is wrong to take more than our share, even if we do not reduce them to disease or destitution, and even if they would willingly waive their rights. When groups are threatened with extortion, we often render their rights inalienable. We should do so here. The rights of our descendants are not ones we would allow them to “waive.”